2020
DOI: 10.2147/idr.s262104
|View full text |Cite
|
Sign up to set email alerts
|

<p>Prescribing Pattern of Antibiotics Using WHO Prescribing Indicators Among Inpatients in Ethiopia: A Need for Antibiotic Stewardship Program</p>

Abstract: Background: Irrational prescribing of antibiotics is a universal public health problem, leading to antibiotic resistance. Understanding the prescribing pattern of antibiotics is crucial to tackling irrational prescription. Yet, comprehensive studies regarding the prescribing pattern of antibiotics among inpatients and the need for an Antibiotic Stewardship Program (ASP) are lacking in Ethiopia. This study aimed to evaluate prescribing patterns of antibiotics and the need for an ASP. Methods: A hospital-based p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
45
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(66 citation statements)
references
References 46 publications
11
45
10
Order By: Relevance
“…83.63% of prescribed drugs were from the essential drugs list. Likewise, Gebre Teklemariam Demoz [11] et al reported that 52.3% of patients had at least one oral and/or injectable antibiotic prescribed. The average number of prescribed antibiotics per patient was 2.01 in their study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…83.63% of prescribed drugs were from the essential drugs list. Likewise, Gebre Teklemariam Demoz [11] et al reported that 52.3% of patients had at least one oral and/or injectable antibiotic prescribed. The average number of prescribed antibiotics per patient was 2.01 in their study.…”
Section: Resultsmentioning
confidence: 99%
“…The average number of prescribed antibiotics per patient was 2.01 in their study. They have also found that the majority (97.6%) of antibiotics were prescribed by their generic name, and all prescribed antibiotics were from the National Essential Medicine List [11].…”
Section: Resultsmentioning
confidence: 99%
“…Comparing the classes of various antimicrobials usage, it was observed that in government cephalosporins (40%) was highly used, followed by penicillins (19%), whereas in the case of private hospital cephalosporins (43%), was followed by aminoglycosides (12.3%). According to an Ethiopian study [3], cephalosporins were the widely used antimicrobials in hospitals followed by ampicillin. A similar pattern is followed in this study and also substantially supported by usage of cephalosporins in studies done in Malaysian [13], while some other studies [11] penicillin's were the most frequently prescribed drug followed by macrolides.…”
Section: Prescribing Pattern Of Antimicrobialsmentioning
confidence: 99%
“…Therefore, antimicrobials require more prudent prescribing, dispensing, and administration [2]. Irrational use of antimicrobials will result in various health hazards [3], such as drug resistance, the increased incidence of side effects, reduced effectiveness of the drug therapy, increased cost of therapy, prolonged hospital stays, and increased morbidity and mortality [4]. WHO expertise provides various methodologies and set of indicators to access drug therapy across the world.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its cost-effective and safety profile, ceftriaxone is one of the most widely used antibiotics in sub-Saharan Africa (SSA) 13 , 14 to treat different types of infections including lung infections, central nervous system infections, bone infections, abdominal infections, skin and soft tissue infections, and urinary tract infections. However, a higher rate of inappropriate use was reported in different studies.…”
Section: Introductionmentioning
confidence: 99%